2013
DOI: 10.1136/thoraxjnl-2012-202785
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of incentive spirometry in patients following thoracotomy and lung resection including those at high risk for developing pulmonary complications

Abstract: Background Following thoracotomy, patients frequently receive routine respiratory physiotherapy which may include incentive spirometry, a breathing technique characterised by deep breathing performed through a device offering visual feedback. This type of physiotherapy is recommended and considered important in the care of thoracic surgery patients, but high quality evidence for specific interventions such as incentive spirometry remains lacking. Methods 180 patients undergoing thoracotomy and lung resection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
98
0
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 28 publications
1
98
0
18
Order By: Relevance
“…[31][32][33]35,37,40 Studies comparing incentive spirometry for PPC prevention after cardiac/thoracic surgery also include a trial with no intervention as the control, 48 and studies that compared incentive spirometry to other techniques. 44,45,47,48,51,52,54,55,58,60 The majority of these trials reported no difference between incentive spirometry and the comparator. 44,47,48,51,52,54,58,60 This creates one of the challenges in evaluating the evidence on incentive spirometry in PPC prevention.…”
Section: Incentive Spirometrymentioning
confidence: 99%
See 4 more Smart Citations
“…[31][32][33]35,37,40 Studies comparing incentive spirometry for PPC prevention after cardiac/thoracic surgery also include a trial with no intervention as the control, 48 and studies that compared incentive spirometry to other techniques. 44,45,47,48,51,52,54,55,58,60 The majority of these trials reported no difference between incentive spirometry and the comparator. 44,47,48,51,52,54,58,60 This creates one of the challenges in evaluating the evidence on incentive spirometry in PPC prevention.…”
Section: Incentive Spirometrymentioning
confidence: 99%
“…44,45,47,48,51,52,54,55,58,60 The majority of these trials reported no difference between incentive spirometry and the comparator. 44,47,48,51,52,54,58,60 This creates one of the challenges in evaluating the evidence on incentive spirometry in PPC prevention. A randomized controlled trial with sufficient numbers should compare any of the techniques to a standard regimen of up and out of bed and early ambulation.…”
Section: Incentive Spirometrymentioning
confidence: 99%
See 3 more Smart Citations